2010
DOI: 10.1007/s00441-010-0978-4
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-derived stem cells: isolation, characterization, differentiation, and application in cell and gene therapy

Abstract: Muscle tissue represents an abundant, accessible, and replenishable source of adult stem cells for cell-based tissue and genetic engineering. A population of cells isolated from muscle exhibits both multipotentiality and self-renewal capabilities. Satellite cells, referred to by many investigators as muscle stem cells, are myogenic precursors that are capable of regenerating muscle and that demonstrate self-renewal properties; however, they are considered to be committed to the myogenic lineage. Muscle-derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
3

Year Published

2011
2011
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 129 publications
(128 reference statements)
3
60
0
3
Order By: Relevance
“…The existence of stem cells has been demonstrated in various adult tissues including brain, bone marrow and peripheral blood, muscle, skin, breast, lung, kidney, liver, pancreas and thyroid gland [96][97][98][99][100][101][102][103][104][105][106][107][108]. However, genes that contribute to the stem cell phenotype and cell differentiation still need to be elucidated.…”
Section: Expression Of P63mentioning
confidence: 99%
“…The existence of stem cells has been demonstrated in various adult tissues including brain, bone marrow and peripheral blood, muscle, skin, breast, lung, kidney, liver, pancreas and thyroid gland [96][97][98][99][100][101][102][103][104][105][106][107][108]. However, genes that contribute to the stem cell phenotype and cell differentiation still need to be elucidated.…”
Section: Expression Of P63mentioning
confidence: 99%
“…Moreover, under proper in vitro condition MDSCs undergo myogenic, cardiogenic, osteogenic, and chondrogenic differentiation. They have also hematopoietic potential [28,41].…”
Section: Multipotent Muscle-derived Stem Cellsmentioning
confidence: 99%
“…PAX3 and PAX7 in satellite cells), whereas other markers are shared among various cell types. There are other limitations, too, such as changes in proliferation rate and cellular multipotency [41]. Moreover, it was demonstrated that these cells display a decreased healing potential when administrated in vivo [56].…”
Section: Isolation and Culture Of Muscle Derived Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations